AB1283 WHEN SHOULD WE EVALUATE CYTOMEGALOVIRUS INFECTION IN IMMUNOSUPPRESSED PATIENTS WITH CONNECTIVE TISSUE DISEASES?. (June 2019) - Nakayama, Yoichi; Sada, Ryuichi; Miyake, Hirofumi; Akebo, Hiroyuki; Tsugihashi, Yukio
Abstract : Background: Cytomegalovirus (CMV) infection is an opportunistic and often problematic infection in patients with connective tissue diseases (CTD patients) who undergoes immunosuppressive therapy. However, in immunosuppressed CTD patients, CMV infection tends to be overdiagnosed, because it manifests with various symptoms and shows organ involvement. Little is known about when to suspect CMV infection and when to conduct CMV pp65 antigenemia assay in immunosuppressed CTD patients. Objectives: To investigate the characteristics of patients who underwent CMV antigenemia assay and identify contributing factors of CMV infection in immunosuppressed CTD patients in a single center of Japan. Methods: Medical records of hospitalized CTD patients who underwent CMV antigenemia assays between April 2015 and July 2018 were retrospectively reviewed. Patients were divided into groups with/without CMV antigenemia. Clinical features, basal immunosuppressive therapies, and laboratory data were analyzed. Results: Overall, 108 patients were enrolled into the study; of these, the positive (group A) and negative (group B) CMV antigenemia groups had 49 and 59 patients, respectively. The underlying CTDs included systemic lupus erythematosus (n=27), anti-neutrophil cytoplasmic antibody-associated vasculitis (n=26), rheumatoid arthritis (n=22), polymyositis/dermatomyositis (n=13), and others (n=20). Glucocorticoid was used in 101 (93.5%) patients, and mean prednisolone dose was 27.1±18.3 mg/day. Pulse glucocorticoid therapy and intravenous cyclophosphamide (IVCY) therapy was administered in 14 (13.0%) and 22 (20.4%) patients, respectively. Group A patients had a significantly higher rate of Charlson Comorbidity Index (CCI) ≥3 (69.4% vs. 30.5%, p<0.001). Mean prednisolone dose was significantly higher in Group A (32.9±15.5 mg/day vs. 22.3±19.0 mg/day, p=0.001). Pulse glucocorticoid therapy (26.5% vs. 1.7%, p<0.001) and IVCY (36.7% vs. 6.8%, p<0.001) were administered significantly more often to Group A patients. Myelosuppression was seen significantly more often in Group A (61.2% vs 39.0%, p=0.035). Laboratory data, including serum lymphocyte counts (1016±1136/μl vs. 1218±718/μl), hemoglobin level (10.5±2.6 g/dL vs. 11.5±2.1 g/dL), and platelet counts (14.5±9.7 ×10 6 /μl vs. 24.1±12.9 ×10 6 /μl) were significantly lower in Group A (p<0.05). Multivariate logistic regression analysis revealed CCI≥3 (odds ratio (OR) =3.21, 95% CI 1.13-9.16) and IVCY therapy (OR=8.89, 95% CI 1.99-39.7) as independent risk factors of CMV antigenemia. The result suggested that pulse glucocorticoid therapy could relate to CMV antigenemia (OR = 9.07, 95% CI 0.96-85.7). Based on the prediction criteria for CMV antigenemia defined as the existence of one or more contributing factors including CCI≥3, pulse glucocorticoid therapy, IVCY, and myelosuppression; sensitivity and specificity were 89.8% (95% CI 81.3-98.3) and 44.1% (95% CI 31.4-56.8), respectively. With contributing factors limited to CCI≥3 and IVCY, sensitivity and specificity became 75.5% (95% CI 63.5-87.5) and 64.4% (95% CI 52.2-76.6), respectively. Conclusion: Having multiple comorbidities and being on intensive immunosuppressive therapy, such as pulse glucocorticoid therapy and IVCY, were related to CMV antigenemia in CTD patients. The prediction criteria, including CCI≥3, pulse glucocorticoid therapy, IVCY, and myelosuppression are helpful to clinically rule out CMV infection. Disclosure of Interests: None declared